Genetic organization of plasmid R1162 DNA involved in conjugative mobilization. - Brasch, M A (1986)
DNA involved in the mobilization of broad-host-range plasmid R1162 was localized to a region of 2.7 kilobases within coordinates 3.4 to 6.1 kilobases on the R1162 map. By examining the transfer properties of plasmids containing cloned fragments of DNA from within this region, we showed that at least four trans-active products and a cis-active site (oriT) were involved in mobilization. A cloned DNA fragment of 155 base pairs was capable of providing full oriT activity. This fragment was located within 600 base pairs of DNA containing the origin of replication of R1162, and its nucleotide sequence and that of neighboring DNA were determined. Activation of oriT required R1162-encoded, trans-acting products. Deletions which resulted in the loss of one or more of these had a variable effect on transfer efficiency and indicated the presence of both essential and nonessential Mob products. Regions encoding these products flanked oriT and in one case appeared to overlap a gene essential for plasmid replication. The implications of these findings with respect to the broad host range of R1162 are discussed.